2022
DOI: 10.1111/1759-7714.14750
|View full text |Cite
|
Sign up to set email alerts
|

FBP1 induced by β‐elemene enhances the sensitivity of gefitinib in lung cancer

Abstract: Background: β-elemene is known to play a critical role in tumorigenesis as well as tyrosine kinase inhibitor (TKI) resistance in lung cancer. However, the biological function and molecular mechanism remain largely unknown. Methods: In this study, the common genes involved in gefitinib resistance and β-elemene were identified using bioinformatic analysis. The expression of FBP1 was examined by qRT-PCR and Western blot analysis. Cell proliferation, flow cytometry, clone formation and IC50 assays were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…MiRNAs are implicated in the pathogenesis of multiple human diseases, and some miRNAs have been reported to modulate chemotherapeutic drug sensitivity of cancer cells (Li et al., 2023; Niu et al., 2019; Xu et al., 2019; Yao & Shi, 2023). MiR‐17‐5p modulates chemoresistance of gastric cancer cells by targeting p21 (Wang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs are implicated in the pathogenesis of multiple human diseases, and some miRNAs have been reported to modulate chemotherapeutic drug sensitivity of cancer cells (Li et al., 2023; Niu et al., 2019; Xu et al., 2019; Yao & Shi, 2023). MiR‐17‐5p modulates chemoresistance of gastric cancer cells by targeting p21 (Wang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC is a deadly human malignancy, and drug development for NSCLC is a hot spot in cancer research (Nguyen et al, 2023;Puri et al, 2023). Notably, some recent published studies have reported that β-elemene represses the malignant biological behaviors of lung cancer cells (Li et al, 2023;Song et al, 2023;Xu et al, 2023;Yao et al, 2014). In this work, we observe that β-elemene decreases the viability of cisplatin-resistant NSCLC cells, which further validates the tumor-suppressive function of β-elemene for NSCLC.…”
Section: On Nsclc Cells Is Partially Reversed By Stat3 Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-elemene is a natural compound that displays antimetastatic efficacy by blocking PKM2 transformation and nuclear translocation [160]. β-elemene can overcome gefitinib resistance by inducing fructose-1,6-bisphosphatase [161]. Licochalcone, a natural compound from Glycyrrhiza uralensis, is a potent HIF-1α inhibitor that can suppress the expression of GLUT1 and PDK1 by inhibiting HIF-1α in HCT116 cells [162].…”
Section: Natural Products Suppressing Other Glycolytic Enzymes and Th...mentioning
confidence: 99%